AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN DAN AKAR ALANG-ALANG (Imperata cylindrica L) TERHADAP BAKTERI Propionibacterium acnes - Adesiti Aminah; Desi Sri Rejeki; Alik Kandhita Febriani (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
The reed plant (Imperata cylindrica L.) is a plant from the Poaceae family which is commonly used by the community as a herbal medicine for the leaves and roots. The benefits of the reed plant include antidiuretic, anti-inflammatory, neuroprotective and antibacterial. Reed plants have bioactive compounds of alkaloids, flavonoids, saponins and tannins that can be developed. This study aims to determine the comparison of antibacterial activity in leaf extracts with concentrations of 30, 40, 50% and alang-alang root samples with concentrations of 10, 15 and 20% against Propionibacterium acnes bacteria. This research is quantitative experimental with a maceration extraction method using 70% ethanol solvent. Testing of the antibacterial activity of the ethanol extract of Alang-alang leaves and roots against Propionibacterium acnes bacteria used the disc diffusion method. Based on the research that has been carried out, the results show that the ethanol extract of Alang-alang leaves and roots contains bioactive compounds in the form of alkaloids, flavonoids, steroids, saponins and tannins. The results of the antibacterial activity test on leaf extracts with concentrations of 30, 40 and 50 showed an inhibition zone of 7.2; 9.1 and 11.2 mm with medium, medium and strong categories. Meanwhile, in root extract samples with concentrations of 10, 15 and 20%, an inhibition zone of 8.1 was obtained; 9.2 and 11.1 mm with medium, medium and strong categories.